N,N-methylene bisacrylamide-crosslinked polyacrylamide for controlled release urea fertilizer formulations - Abraham J; Pillai V N R (Communications in Soil Science and Plant Analysis, 1995)
Controlled release urea fertilizers based on N,N-methylene bisacrylene (NNMBA) - crosslinked polyacrylamide soil conditioner are described. Laboratory preparation and evaluation of coated urea fertilizers were conducted. Urea was initially coated with the copolymer of acrylamide and NNMBA. Ethylene vinylacetate (EVA), natural rubber (NR), and polyvinylchloride (PVC) were compared with polystyrene (PS) for their suitability to be used as sealant material in coating fertilizer urea with the copolymer of acrylamide and NNMBA. The coated system with EVA had a greater slow release character than that with PS while NR and PVC systems had a lesser slow release character.
Keywords: Urea fertilizer